IMPROVING STUDENTS VOCABULARY MASTERY THROUGH CHARADES GAME AT SMA NEGERI 1 MAUMERE - RAMADHAN, PUTRA; ALINDA, MARTA; ENI , GENOVEVA DUA (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2025)
This research explores the impact of the Charades game on vocabulary mastery among twelfth-grade students at SMA Negeri 1 Maumere. Utilizing a classroom action research design, the research was conducted in two cycles, each comprising planning, action, observation, and reflection stages. The observations findings indicated that students faced challenges in vocabulary acquisition due to monotonous teaching methods that happened during learning process, resulting in low engagement and motivation during English lessons. The implementation of the Charades game aimed to address these issues by creating a more interactive and enjoyable learning environment. The results of this research showed a significant improvement in students' vocabulary scores, with average scores increasing from 52.92 in the pre-test to 71.81 in the final post-test. Additionally, the number of students achieving passing scores were increased. The findings suggest that incorporating engaging activities like Charades can enhance vocabulary learning and foster greater student enthusiasm in language acquisition. ABSTRAKPenelitian ini mengeksplorasi dampak dari permainan tebak kata terhadap penguasaan kosakata di antara siswa kelas dua belas di SMA Negeri 1 Maumere. Dengan menggunakan desain penelitian tindakan kelas, penelitian ini dilakukan dalam dua siklus, yang masing-masing terdiri dari tahap perencanaan, tindakan, observasi, dan refleksi. Temuan observasi menunjukkan bahwa siswa menghadapi tantangan dalam penguasaan kosakata karena metode pengajaran yang monoton, yang mengakibatkan rendahnya keterlibatan dan motivasi selama pelajaran bahasa Inggris. Implementasi permainan tebak gesture bertujuan untuk mengatasi masalah ini dengan menciptakan lingkungan belajar yang lebih interaktif dan menyenangkan. Hasil dari penelitian ini menunjukkan peningkatan yang signifikan pada nilai kosakata siswa, dengan nilai rata-rata meningkat dari 52,92 pada pre-test menjadi 71,81 pada post-test akhir. Selain itu, jumlah siswa yang mencapai nilai kelulusan juga meningkat. Temuan ini menunjukkan bahwa menggabungkan kegiatan yang menarik seperti Tebak gestur dapat meningkatkan pembelajaran kosakata dan menumbuhkan antusiasme siswa yang lebih besar dalam penguasaan bahasa.